(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2023)
Based on specimens collected recently in the Uruguay river, downstream of Salto and Concordia cities, in this note we present the first record of Hypostomus ternetzi for the lower Uruguay river basin.